Effect of Different Factors on the Success of Tender Shoot Cleft Grafting in Chilgoza (Pinus gerardiana Wall) - Singh, N. B. (Indian Forester, 1992)
Four factors, namely time of grafting, age of clone, age of root-stock, and age of scion, have direct bearing on the success of tender-shoot-cleft-grafting on Chilgoza. February is the best period which gives 65-70% success, followed by medium-size of tree (less than one metre girth), two and half years old root-stock and two years old scion.